2019
DOI: 10.1039/c8me00074c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of spheroidal triblock Janus nanoparticle solutions in nanotubes

Abstract: We have performed coarse-grained molecular simulations to investigate the morphologies and phase diagrams of self-assembled spheroidal triblock Janus nanoparticles (JNPs) confined in nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These structures include tripods, tetrapods, and hexapods. Analogous to references [149,150], self-assembly of Janus particles in a two-dimensional confinement has been reported by Baran et al [151,152] using MC simulations with implicit solvent conditions and MD simulations [153]. Self-assembly of Janus particles confined in a cylindrical channel with circular harmonic trap has been reported using MD simulations [148].…”
Section: Self-assembly In External Fieldmentioning
confidence: 57%
See 1 more Smart Citation
“…These structures include tripods, tetrapods, and hexapods. Analogous to references [149,150], self-assembly of Janus particles in a two-dimensional confinement has been reported by Baran et al [151,152] using MC simulations with implicit solvent conditions and MD simulations [153]. Self-assembly of Janus particles confined in a cylindrical channel with circular harmonic trap has been reported using MD simulations [148].…”
Section: Self-assembly In External Fieldmentioning
confidence: 57%
“…Self-assembly of colloids under spatial confinement can be exploited to induce orientation-dependent interactions [148][149][150][151]. Self-assembly of spherical diblock and spheroidal triblock Janus nanoparticle solutions confined in a nanotube were studied using DPD framework [149,150]. The inner surface of the confining tube was either hydrophilic or hydrophobic or hydroneutral.…”
Section: Self-assembly In External Fieldmentioning
confidence: 99%
“…where ρ wall is the number density of the NT wall, a wall is the interaction parameter between the wall and the DPD bead, R is the normal vector from the wall surface to the bead, and R = |R|. To avoid unphysical overlapping of the beads into the wall of the NT at high pressure, ρ wall was set at 10.0 based on our previous studies [19][20][21]. In this study, we adopted the hydrophilic NT wall as shown in table 1.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Confinement to nanoscale space is another way to change the self-assembled structure of NPs, and it is known to produce unique structures and properties that differ from those of bulk [19][20][21]. Wu et al [22] investigated the morphology of charged silica NPs dispersed or confined in microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Designing colloidal particles with anisotropic shapes and chemical interactions is an effective method to control the morphologies of self-assembled NPs. [13][14][15][16] Janus NPs are one of the unique anisotropic NPs. They have received considerable attention because of their physical characteristics due to at least two distinct chemical or physical surfaces.…”
mentioning
confidence: 99%